Combination of modified mixing technique and low frequency ultrasound to control the elution profile of vancomycin-loaded acrylic bone cement. Issue 2 (February 2016) - Wendling, A.; Mar, D.; Wischmeier, N.; Anderson, D.; McIff, T.
Abstract : Objectives: The objective of this study was to determine if combining variations in mixing technique of antibiotic-impregnated polymethylmethacrylate (PMMA) cement with low frequency ultrasound (LFUS) improves antibiotic elution during the initial high phase (Phase I) and subsequent low phase (Phase II) while not diminishing mechanical strength. Methods: Three batches of vancomycin-loaded PMMA were prepared with different mixing techniques: a standard technique; a delayed technique; and a control without antibiotic. Daily elution samples were analysed using flow injection analysis (FIA). Beginning in Phase II, samples from each mix group were selected randomly to undergo either five, 15, 45, or 0 minutes of LFUS treatment. Elution amounts between LFUS treatments were analysed. Following Phase II, compression testing was done to quantify strength. A-priori t -tests and univariate ANOVAs were used to compare elution and mechanical test results between the two mix groups and the control group. Results: The delayed technique showed a significant increase in elution on day one compared with the standard mix technique (p < 0.001). The transition point from Phase I to Phase II occurred on day ten. LFUS treatments significantly increased elution amounts for all groups above control. Delayed technique resulted in significantly higher elution amounts for the five-minute- (p = 0.004) and 45-minute- (p < 0.001) duration groups compared with standard technique. Additionally, the correlations between LFUS duration and total elution amount for both mix techniques were significant (p = 0.03). Both antibiotic-impregnated groups exhibited a significant decrease in offset yield stress compared with the control group (p < 0.001), however, their lower 95% confidence intervals were all above the 70 MPa limit defined by International Standards Organization (ISO) 5833-2 reference standard for acrylic bone cement. Conclusion: The combination of a delayed mix technique with LFUS treatments provides a reasonable means for increasing both short- and long-term antibiotic elution without affecting mechanical strength. Cite this article: Dr. T. McIff. Combination of modified mixing technique and low frequency ultrasound to control the elution profile of vancomycin-loaded acrylic bone cement. Bone Joint Res 2016;5:26–32. doi: 10.1302/2046-3758.52.2000412